DIKSI DALAM TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 11 PADANG - Tenesia, Tevani; Thamsin, Andria Catri (Universitas Negeri Padang, 2019)
ABSTRACT This research is motivated by the problems in writing description texts of seventh grade students at SMPN 11 Padang. This type of research is qualitative research using descriptive methods. The data from this study is the use of diction in the description text of SMPN 11 Padang students. The data sources used in this study are the sentences in the description text written by seventh grade students of SMPN 11 Padang. The researcher only discussed and examined 30 description text writtings written by seventh grade students of SMPN 11 Padang. Based on the results of the study, the following points can be concluded. First, the description text of class VII of SMPN 11 Padang in the use of diction is more dominant having accurary, precision, and harmony in word selection. This can be proven from 30 student description texts consisting of 96 paragraphs, 332 sentences, and 3,567 dictionaries. There are 3.126 accurary in word selection, 3,507 precision in word selection, and 3,494 harmony in word selection. Second, from the student’s description text, it can be seen that there are still students who don’t understand about the use of diction. It can be seen from 3,567 diction used, there are still innaccuracies in the diction as much as 441 words, the accuracy of diction is 60 words, and the incompatibility of diction is 73 words. Third, students still don’t understand the use of spelling in accordance with the Indonesian spelling rules. Kata kunci : Kualitatif, Menulis, Teks Deskripsi, Diksi